Can the Intestine Perform Some Functions of the Kidney? - Uday Sankar Chatterjee; Gopal Samanta; Pallab Pradhan; Provat K. Samanta; Tapan K. Mondal (The Scientific World Journal)
The majority of patients in countries like India and Pakistan with end-stage renal disease (ESRD) die without renal replacement therapy due to lack of adequate resources. The use of the intestinal mucosa as a semipermeable membrane for removal of urea and creatinine from the body has been previously studied using various types of intestinal lavage for gut dialysis. This study was undertaken in an animal model to assess the applicability, cost of therapy, and acceptability of the method for potential application in humans. Renal failure was induced in six dogs by bilateral ureteric ligation along with six healthy controls. Dialysis fluid was introduced per rectum as an enema, which was repeatedly administered. Clearances of serum creatinine and urea were assessed. Mean recovery of creatinine and urea in dialysate in the present study was around 8.925 mmol/l and around 207.74 μmol//l, respectively. The mean clearances of serum creatinine and urea were, respectively, 0.0683 and 0.0633 ml/sec. Enteral dialysis was effective and, considering its minimal cost (monthly cost will be around US$35–40) vis a vis available methods, it holds promise for the treatment of patients with ESRD. The creation of an appendicostomy for repeated introduction of antegrade enemas would be a consideration.